2008
DOI: 10.1038/jp.2008.23
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to NICU transfusion guidelines: data from a multihospital healthcare system

Abstract: Objective: We critically reviewed every NICU blood component transfusion (packed erythrocytes, platelets, frozen plasma (FP) and cryoprecipitate) administered during a one-year period. This was done to determine the proportion of transfusions given out of compliance with the Intermountain Healthcare transfusion guidelines, and to look for patterns of noncompliance that could be addressed by quality improvement measures. Result: During 2006 the three NICUs cared for 1759 neonates. Seventeen percent of these rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 23 publications
0
52
1
1
Order By: Relevance
“…None of these erythrocyte or platelet transfusions were for treatment of hemorrhagic complications; rather, all were prophylactic, meaning that the hemoglobin, hematocrit or platelet count fell below the transfusion 'trigger' level. 12 The transfusions were finished 18 ± 12 h before the Anderson tube was placed. One patient had two episodes of supraventricular tachycardia as antecedents of the NEC, each being successfully treated with adenosine but not with ice to the face.…”
Section: Resultsmentioning
confidence: 99%
“…None of these erythrocyte or platelet transfusions were for treatment of hemorrhagic complications; rather, all were prophylactic, meaning that the hemoglobin, hematocrit or platelet count fell below the transfusion 'trigger' level. 12 The transfusions were finished 18 ± 12 h before the Anderson tube was placed. One patient had two episodes of supraventricular tachycardia as antecedents of the NEC, each being successfully treated with adenosine but not with ice to the face.…”
Section: Resultsmentioning
confidence: 99%
“…Petäjä et al [32] reported that only about 35% of platelet transfusions given were compliant with previously agreed upon guidelines. In the Intermountain Healthcare System, we audited all NICU transfusions given during the year 2006 and determined that about 65% of platelet transfusions were compliant with our guidelines, thus 35% were not [33] . In January 2009, we initiated a system-wide program aimed at increasing compliance with transfusion guidelines.…”
Section: Compliance With Platelet Transfusion Guidelinesmentioning
confidence: 99%
“…In brief, the guidelines recommend transfusion if the hematocrit falls below 35% for a patient on mechanical ventilation, below 27% for a patient on supplemental oxygen or with signs of anemia but not on mechanical ventilation and below 20% in any NICU patient. Compliance with these guidelines for the year 2006 was 70%, 4 and compliance for the year 2009 was 90%. 5 When NEC was identified, radiographic images, radiographic reports and physician's notes pertaining to NEC were reviewed.…”
Section: Methodsmentioning
confidence: 99%